GMO 리스크 커뮤니케이션 전략수립을 위한 정책연구 - 황윤재 (한국농촌경제연구원, 2009)
Korean consumers' confidence in Genetically Modified(GM) foods is low, and there is a notable gap between consumers and experts related to the perception toward the safety of Genetically Modified Organisms(GMO). This situation could be solved by setting out risk communication strategies which enable related parties to exchange risk information and communicate with each other in an effective manner. This study has the purpose of understanding the general Korean public's view on generally modified foods and consumers' perception toward them. Understanding the internal and external communication status on food risks including GMO and identifying current issues in this area also constitute the purpose. The strategies to improve consumers' awareness of genetically modified foods through effective risk communications and to resolve ungrounded misunderstanding were also pursued as an objective of this study. To fulfill the purposes described above, Chapter 2 focuses on explaining risk communication's concept and features. Chapter 3 shows key country examples of GMO risk communication including EU, Austria, Japan and the United States. Chapter 4 identifies problems in GMO risk communication based on the understanding of GMO trend and risk communication status in Korea. Lastly, Chapter 5 presents the risk communication strategies for GMO. Risk communication involves interactive process of exchanging risk-related information among individuals, groups and organizations. It could be conducted in various ways using various means to fulfill the objectives of disclosing and delivering information, collecting information, listening to opinions, promoting participation and mutual understanding, and building policy consensus and partnership. The ever complicated and diversified society amplifies the variety and complexity of the risk factors that could have harmful effects on humans. The reach of the ripple effects has been wider than before. Accordingly, the general public's demand for risk information is rapidly increasing. Yet, individuals encounter difficulty in selecting necessary information out of the flood of information. This has made the role of the risk communication and the government more important. Online and offline media are the main sources of information for consumers and have a considerable impact on the public opinion. The analysis of the media coverage on GMO and articles have found that GMO related issues mainly include GMO safety, vague fear of GMO, possibility of proliferation of anti-GMO importation sentiment, GMO safety for animal feeds, government's unified supervision, unstandardized usage of GMO terms, and identity confusion in food safety related organizations. Former studies indicate that Koran consumers' level of GMO awareness is very high, but their understanding is not that accurate. In terms of socio-economic aspect, Korean consumers agree on the need and usage of GMO to a certain extent. Nevertheless, their perception toward GMO is still negative. In addition, they don't much rely on government agencies as a source of information on food safety management. Their trust in the agencies tends to be low when it comes to GMO. The Korean government has provided GMO related information and promoted its safety on the website. It has not only held information sessions or steering meetings but also produced and distributed reports, various printed materials and videos. Likewise, the government has adopted multiple tools and means to stimulate GMO risk communication. Nevertheless, efficient communication has not taken place so far owning to 1) consumers' lack of understanding of GMO and low confidence in government agencies; 2) lack of joint activities between related government departments and agencies; 3) lack of expertise, systematic operation and contents; 4) insufficient two-way communications; and 5) unstandardized usage of GMO terms. Hence, overall improvement of the existing GMO risk communication scheme, methods and strategies is essential for more efficient and effective communication. Even experts are divided surrounding the safety of genetically modified foods. In this regard, the attempt to directly persuade the nation to believe the GMO safety based on scientific grounds should be restrained. Rather, it is more desirable to take an indirect way of persuading by focusing on "economic value", "usability" and "food safety" of GMO and to lead the gradual change in the national perception and attitude toward GMO. To ensure more efficient risk communication for GMO, first, an organization dedicated to risk communication should be established. Second, a communication training program should be prepared to nurture experts in this field. Lastly, agencies related to GM agricultural, forestry and fishery products under the Ministry for Food, Agriculture, Forestry and Fisheries should work together internally(inside the government) and externally with other governments(outside the government). In relation to the strategies above, the following action plans are suggested: 1) designing programs to change perceptions toward GMO in order to reinforce the government agencies' capability to respond; 2) producing basic GMO communication materials based on the joint inter-agency partnership for consistent communication; 3) expanding risk communication via online channel by strengthening consumer monitoring activity, providing information via email and building web-based educational programs; and 4) boosting mutual understanding through face-to-face exchange of opinions; and 5) performing systematic and consistent risk communication based on the risk communication manuals and ensuring prompt response in time of risk occurrence. Researchers: Hwang Yun-Jae, Youn Gue-Young and Han Jae-Hwan Research period: 2008. 12. - 2009. 3. E-mail address: yjhwang@krei.re.kr